Are facility service delivery models meeting the sexual and reproductive health needs of adolescents in Sub-Saharan Africa? A qualitative evidence synthesis - Yusupha Sanyang; Saikou Sanyang; Alice Norah Ladur; Mamady Cham; Nicola Desmond; Florence Mgawadere (BMC Health Services Research)
Abstract Background Adolescents in Sub-Saharan Africa (SSA) face significant health and social challenges related to sexual and reproductive health (SRH), including unwanted pregnancies, unsafe abortions, and sexually transmitted infections (STI). Barriers to information and services are compounded by lack of access to appropriate information, fear of being judged, health provider attitudes and contextual factors such as culture, religion, poverty, and illiteracy. Facility-based service delivery models for adolescents offer a structured environment and provide an opportunity to deliver such information and services. The review critically examined how well these models meet the SRH needs of adolescents in SSA. Methods A systematic search was conducted using five databases: Web of Science, MEDLINE, Scopus, PubMed, and Google Scholar. The Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines were followed to maintain transparency and completeness. Covidence software was used for screening and data extraction, and NVIVO 12 PRO was used to manage the analysis. A narrative synthesis using Thomas and Harden’s thematic analysis was used to identify themes. Results The search yielded 14,415 articles, and 20 papers met the inclusion criteria and were included in this review. From the findings, adolescents expressed the need for comprehensive SRH information, adolescent-friendly facilities, parental and male involvement, and respectful healthcare providers. Three facility-based adolescent-friendly SRH delivery models are used in SSA: Stand-alone clinics, Youth-friendly corners, and Integrated/mainstreamed models. Adolescent-friendly interventions, friendly staff, and accessibility were reported as facilitators to services meeting the needs of adolescents and promoting positive experiences. However, several barriers were identified: negative attitudes of health workers, financial constraints, transportation challenges, waiting time, intimidating environments, and lack of confidentiality pose a challenge to the effectiveness of the model. Conclusion Facility-based SRH service delivery models can improve access to information and services when complemented with community-based interventions, adolescent-friendly providers, and assurance of service accessibility. However, significant gaps, such as healthcare providers' negative attitudes and behaviours, concerns about privacy and confidentiality, financial constraints, and transportation challenges, limit their effectiveness. These findings call for expanding out-of-facility services, adopting mHealth solutions, enhancing provider training, strengthening confidentiality, and reducing financial barriers to ensure equitable and effective access to services.